MODERNISATION TECHNOLOGY OF INDUCTION MOTORS USING INTERNAL CAPACITANCE REACTIVE POWER COMPENSATION - Chuenko, R. (Energy and Automation, 2016)
The modernisation technology of induction motors using internal capacitance reactive power compensation is offered